INDONESIAN EDUCATION, PISA SCORES AND 3 READING STRATEGIES THAT WORK - BERYL EXLEY (Sriwijaya University Learning and Education International Conference, 2016)
This presentation introduces me and my engagement with Indonesian contexts of teaching andlearning. I then introduce the Organization for Economic Cooperation and Development’s (OECD)“Programme for International Student Assessment” (PISA), noting the challenges facing Indonesia inthis period of reform. Publically acknowledging the challenges is an important step in narrowing theagenda and effecting positive future changes. Based on this information from the PISA data, Iintroduce three effective reading strategies that can be used in all years of schooling: (i) summarisingnon-literary texts to get the main detail; (ii) reading figurative language in literary texts; and (iii)actively reading to make meaning from the unwritten ellipses.